WANPRESTASI PIHAK CV. DIRGANTARA AMERTA INDONESIA DALAM PERJANJIAN JUAL BELI BESI HOLLOW DENGAN PIHAK PT ARONI DUTA INDO UTAMA DI KOTA PONTIANAK - NURIL RIZKIQ AULAITA NIM . A1011191246 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Sale and purchase agreements are routine activities of the Indonesian people in their daily lives. The agreement creates rights and obligations for buyers and sellers. The implementation of the Hollow iron sale and purchase agreement between PT Aroni Duta Indo Utama and CV Dirgantara Amerta Indonesia in Pontianak City is made in writing by both parties which has legal force that binds both parties and is valid and applies as a law for both parties. The agreement gives rise to legal relations between the two parties regarding rights and obligations which are the most important part of the agreement. There are times when in this sale and purchase agreement does not fulfill the achievement so that default occurs.In this study, the author formulates the problem of